Afro-Latinx digital connections - Arriaga Arango, Eduard; Villar, Andrés (Reframing Media, Technology, and Culture in Latin/o America., 2021)
"This volume presents examples of how digital technologies are being used by people of African descent in South America and the Caribbean as a means to achieve social justice and to challenge racist images of Afro-descendant peoples"--